2016
DOI: 10.1002/2016gl068548
|View full text |Cite
|
Sign up to set email alerts
|

Vertical variation of ice particle size in convective cloud tops

Abstract: A novel technique is used to estimate derivatives of ice effective radius with respect to height near convective cloud tops (dre/dz) from airborne shortwave reflectance measurements and lidar. Values of dre/dz are about −6 μm/km for cloud tops below the homogeneous freezing level, increasing to near 0 μm/km above the estimated level of neutral buoyancy. Retrieved dre/dz compares well with previously documented remote sensing and in situ estimates. Effective radii decrease with increasing cloud top height, whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
24
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 60 publications
3
24
1
Order By: Relevance
“…Additionally, the results also confirm that although retrievals of effective radius using multi near-infrared wavelengths result in particle sizes from different cloud altitudes, this conventional retrieval technique only provides information on the cloud-top effective radius. This is due to the fact, that the retrieved r eff represents a vertically weighted value where cloud top layers are weighted at most, which is in agreement with analyses reported by Chang and Li (2002), Chang and Li (2003), Zhang et al (2010), King and Vaughan (2012), , King et al (2013), and van Diedenhoven et al (2016. Table 4 summarizes the mean ± standard deviation η of effective radius from r eff and r * eff,w , and the weighting-altitude z * w for multi near-infrared wavelengths between 1240 nm -3700 nm.…”
supporting
confidence: 75%
See 2 more Smart Citations
“…Additionally, the results also confirm that although retrievals of effective radius using multi near-infrared wavelengths result in particle sizes from different cloud altitudes, this conventional retrieval technique only provides information on the cloud-top effective radius. This is due to the fact, that the retrieved r eff represents a vertically weighted value where cloud top layers are weighted at most, which is in agreement with analyses reported by Chang and Li (2002), Chang and Li (2003), Zhang et al (2010), King and Vaughan (2012), , King et al (2013), and van Diedenhoven et al (2016. Table 4 summarizes the mean ± standard deviation η of effective radius from r eff and r * eff,w , and the weighting-altitude z * w for multi near-infrared wavelengths between 1240 nm -3700 nm.…”
supporting
confidence: 75%
“…For non precipitating ice 25 clouds, ice crystal sizes typically decrease as a function of altitude (van Diedenhoven et al, 2016;Heymsfield et al, 2017).…”
Section: Forward Simulation Of Vertically Inhomogeneous Cloudsmentioning
confidence: 99%
See 1 more Smart Citation
“…Except for CWP=0 and RR=0, a consistent increase in r ei is found for increasing T ci . A flattening in the reduction in r ei for T cld <210K occurs and is similar to the results of van Diedenhoven et al (2016). While this region is sensitive to the 6 K cut-off used to filter questionable retrievals near the tropopause, the profile in Fig.…”
Section: Differences In R Ei Between Opaque and Transparent Cloudssupporting
confidence: 63%
“…Using a simultaneous retrieval of ice cloud properties from the MODIS and POLDER 20 instruments, van Diedenhoven et al (2014) found that r ei is larger in stronger convective events compared to others at a given cloud top pressure. van Diedenhoven et al (2016) used in situ aircraft observations to show that r ei decreases with height, reaches a minimum around 14 km, and may subsequently increase at higher altitudes. Barahona et al (2014) obtained an increase of a few µm for clouds colder than 195 K with GEOS-5 and Hong and Liu (2015) show similar results with DARDAR data for the thickest convective clouds above 10 km.…”
Section: Insight Into Convective Processes With Amsrmentioning
confidence: 99%